Development and validation of a quality of life instrument for patients with laryngeal cleft. (May 2018) - Irace, Alexandria L.; Walker, Ryan D.; Kawai, Kosuke; Maddock, Meaghan; Dombrowski, Natasha D.; Sideridis, Georgios; Ferrari, Lynne; Rahbar, Reza
Abstract: Objective: To develop and validate a novel pediatric health-related quality of life (HR-QoL) instrument for patients with laryngeal cleft and their families. Methods: We surveyed primary caregivers of patients that underwent endoscopic repair of Type I or II laryngeal cleft. The proposed HR-QoL instrument consists of 40 items representing four domains, assessing the patient's physical symptoms, the patient's and family's social functioning, and the family's emotions regarding the patient's illness pre- and post-operatively. Confirmatory factor analysis was employed to assess construct validity, dimensionality, and optimal simple structure. Results: Of 78 eligible participants reached by phone, 40 (51%) of them completed the questionnaire. Confirmatory factor analysis suggested that all four measured constructs were well supported by the measured items in comparison to a unidimensional model. All factor loadings and factor correlations were significant and factor correlations ranged between 0.723 and 0.879. Indices of test-retest reliability and internal consistency reliability were well above recommended standards. There was a significant correlation between current instrument and PedsQL™ score. The overall QoL score significantly improved from 112.3 (±28.1) before surgery to 158.0 (±28.5) after surgery (mean difference 45.7; 95% CI: 37.3, 54.1; p < 0.001). Conclusion: Our proposed pediatric HR-QoL instrument is a valid tool for measuring quality of life in patients with laryngeal cleft and their families. This instrument can provide insight into the effects of medical and surgical therapy and guide pre- and post-operative management of laryngeal cleft.